Antiplasmodial and Cytotoxic Activity of Piper Piedecuestanum Trel. and Yunck (2018)
ABSTRACT: Background and Objective: Plasmodium resistance to antimalarial drugs has expanded and intensified, making new and effective antimalarial drugs urgently. The objective of this work was the in vitro evaluation of antiplasmodial activity of extracts of different polarity and compounds of the species P. piedecuestanum. Materials and Methods: The plant materials were obtained through successive extractions using solvents of different polarity such as hexane (H), dichloromethane (D), ethyl acetate (A) and methanol (M) and separations techniques for fractionation and isolation of compounds. The antiplasmodial activities of the extracts and compounds were evaluated by SYBR Green I® method and evaluated the cytotoxicity in the cell lines U-937, HUVEC by the MTT method. Results: The antiplasmodial and cytotoxic activity of the extracts of dichloromethane (PPD) and ethyl acetate (PPAE) with antiplasmodial activity of IC50 = 17.93 µg mLG1 ; IS = 2.093 and IC50 = 19.5 µg mLG1 ; IS = 0.791, respectively are reported for the first time. In addition, from P. piedecuestanum species were isolation and characterization five metabolites 5,8-Hydroxy-7-methoxyflavone(1), 6,7-dimethoxy-5,8- dihydroxyflavone(2), 6,7-dimethoxy-5-hydroxyflavone (mosloflavone) (3), 5,6-dihydroxy-7-methoxyflavone (negletein) (4), 5-hydroxy-7- methoxyflavone (5) and a brominated derivative from (5) named 6,8 bromo-5-hydroxy-7-methoxyflavone(7). Compound (1) presented promising antiplasmodial activity with an IC50 = 7.325 µg mLG1 (25.69 µM); ISHUVEC =13.65. Conclusion: Chemical analysis of extracts and compounds from P. piedecuestanum spices will play a central role in the development and modernization of an antimalarial herbal traditional in Colombia.